2021
DOI: 10.5902/1980509822318
|View full text |Cite
|
Sign up to set email alerts
|

Alterações fisiológicas em mudas de <i>Eucalyptus grandis</i> (Hill) ex Maiden submetidas à fertilização nitrogenada e ação do etileno

Abstract: A fertilização e a rustificação durante a produção das mudas de espécies lenhosas promovem alterações morfofisiológicas que potencializam o crescimento e minimizam os danos por estresse após o plantio a campo. O experimento objetivou avaliar a fertilização nitrogenada durante a produção e quantificar as alterações na morfogênese após a aplicação de etileno em mudas de Eucalyptus grandis (Hill) ex Maiden. O experimento foi conduzido em casa de vegetação localizada sob as coordenadas 24°33’ S e 54°04’ O, em deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Recent studies, such as that conducted by Pandolfi et al (2016) with maize plants and Kamanga et al (2020) with tomato, have shown that pre-exposure to moderate stress prepares plants against subsequent stress events. This technique is called hardening, a specific acclimatization process that causes morphophysiological changes in plants that enhance growth and minimize stress damage after field transplanting (Schulz et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies, such as that conducted by Pandolfi et al (2016) with maize plants and Kamanga et al (2020) with tomato, have shown that pre-exposure to moderate stress prepares plants against subsequent stress events. This technique is called hardening, a specific acclimatization process that causes morphophysiological changes in plants that enhance growth and minimize stress damage after field transplanting (Schulz et al, 2021).…”
Section: Introductionmentioning
confidence: 99%